OPTIMALISASI PENERAPAN METODE DISKUSI KELOMPOK UNTUK MENINGKATKAN HASIL BELAJAR EKONOMI DENGAN MATERI POKOK EKONOMI DAN SISTEM EKONOMI PADA SISWA KELAS X.3 SEMESTER SATU SMA NEGERI 3 SUKOHARJO TAHUN PELAJARAN 2014/2015 - Rochmiatun Rochmiatun (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2016)
The research aim was to describe the improvement of grade X.3 SMA N 3 (State Senior High School) student’s economic learning outcome through group discussion method. The respondents of this research were 32 Grade X.3 students of SMA N 3 Sukoharjo. The research was conducted in two cycles, every cycle had four steps. The steps were (1) planning, (2) acting, (3) observing, (4) reflecting. The results of this action research were divided in two cycles. In the first, cycle students average score was 70,31 higher than before. In the second cycle, students average score was 79,59. Based on those results, the implementation of group discussion method improved the learning outcome of grade X.3 students of SMA N 3 Sukoharjo in the economic subject.Keywords : Group Discussion Method, Learning Outcome, Economic